Kangaroo Mother Care as an Effective Strategy to Reduce Pain Responses in Neonates Undergoing Blood Sampling for Congenital Hypothyroidism Screening - Intan Mutiara Hawa; Ida Widiawati; Djudju Sriwenda; Desi Hidayanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The collection of blood samples for Congenital Hypothyroidism Screening (CHS) is a routine neonatal procedure that induces moderate pain, thereby requiring effective interventions to reduce discomfort. This study aimed to examine the effect of the kangaroo method on neonatal pain scores during CHS blood sampling. A quasi‑experimental design with a posttest‑only control group approach was employed, involving 56 neonates selected through quota sampling at Garuda and Ibrahim Adjie Primary Health Centers in Bandung. Pain intensity was assessed using the Neonatal Infant Pain Scale (NIPS) and analyzed with an independent sample t‑test. The findings demonstrated a significant difference between groups, with the intervention group showing a mean pain score of 2.83 compared to 5.79 in the control group. Statistical analysis confirmed a significant effect of the kangaroo method in reducing neonatal pain scores (p = 0.000; p < 0.05). The analgesic mechanism of the kangaroo method operates through the modulation of dual neural pathways that inhibit pain impulses, thereby decreasing neonatal pain responses. These results indicate that the kangaroo method is an effective, practical, and safe non‑pharmacological intervention for reducing neonatal pain during CHS blood sampling and can be recommended for routine pain management in neonatal care.Keywords: kangaroo method; pain; congenital hypothyroidism screening